SUBLEASE AND LEASE WAIVER OF AGRARIAN REFORM LANDS - Qader, Hiwa Ibrahim (Journal of Duhok University, 2018)
The multiplicity and dispersal of the legislation regulating the rent of agrarian reform lands and the different legal situation in the Kurdistan Region than in Iraq led to many difficulties in application and violation of the provisions of the law, so we chose this subject to discuss the extent of the legality for sublease and lease waiver of agrarian reform lands and determine the competent authority to resolve disputes, by following the analytical approach. Among the findings of the research is the permissibility of sublease of agrarian reform lands unless there is an agreement or agricultural custom that prevents this. And in spite of cases regulating by the Law no.24 in the year of 2013, the rule in Iraqi Law is the permissibility of waive the lease of such lands unless there is an agreement or agricultural custom to prevent it. In the light of the research, we recommended to prohibit the rent of agrarian reform lands only after the approval of the Ministry of Agriculture. We also recommended the prevention of waiver of the rent of these lands and the issuance of a law to regulate the rent of agrarian reform lands in Kurdistan Region, and reestablishment the agrarian courts in Iraq and Kurdistan Region